Attitudes and perceptions regarding metabolomics research on HIV and AIDS: Towards a dynamic model relating basic beliefs, technology and behaviour - Henk Jochemsen; Honey Nonyane; Carolus Reinecke; Johan Zaaiman (Koers : Bulletin for Christian Scholarship, 2014)
The human immunodeficiency virus (HIV) and acquired immunodeficiency syndrome (AIDS) pandemic are hitting hard in Africa, not the least in South Africa. In addition to preventative measures, better ways of treatment and delaying the onset of symptoms are still urgently required. Recent developments in biomedicine in South Africa, notably genomics and metabolomics, could well contribute to more effective treatments and diets. However, these technologies are rooted in modern Western culture and may embody concepts and values that are foreign to people with a different culture and worldview in semi-urban communities in South Africa. How can those technologies be introduced into such communities in an ethically acceptable and effective way? To begin answering this question, we conducted qualitative research amongst representatives of such a community near Potchefstroom, South Africa. The results indicate that the worldview, belief system and cultural customs of these people significantly influence the interpretation of HIV and AIDS and their treatment. The results led us to expand an earlier theoretical version of a qualitative model relating cultural factors and worldview to individual behaviour into an empirically informed, dynamic model that envisages possible influences of the introduction of new technologies on the belief and behavioural system of the community.